Influência de Toxoplasma gondii (cepas RH e ME49) na modulação da apoptose de células trofoblásticas (Linhagem BeWo) - Angeloni, Mariana Bodini (2013)
During pregnancy was observed a control in trophoblastic cell proliferation and apoptosis. However, alterations of apoptosis during pregnancy are associated with abnormal placental morphology and function. Toxoplasma gondii is able to modulate trophoblastic cell apoptosis and this modulation is associated with the strain type of the parasite. Therefore the aim of this study was measure the production of cytokines by trophoblastic cells (BeWo cell line), infected with a highly virulent RH strain or a moderately virulent ME49 strain of T. gondii. Also, were analyzed the apoptosis index and death receptor Fas/CD95 expression in trophoblastic cells after infection with both strain types of T. gondii and treated with different cytokines. For this, cells were infected with RH or ME49 strain at 5 parasites: cell ratio, for 2 and 24 hours, the supernatants were collected and the cytokines production was measured. Besides that, cells were treated with pro and anti-inflammatory cytokines, infected with both strain types of T. gondii and were analyzed for apoptosis index by immunohistochemistry and for Fas/CD95 expression by flow cytometry. Besides that western blotting for the detection of the proteins ERK1/2 and survivin (IAP) were done. In both times of infection analyzed ME49-infected BeWo cells exhibited a predominantly pro-inflammatory response profile, whereas cells infected with RH strain showed a higher production of anti-inflammatory cytokines. Besides that, were observed that the incidence of apoptosis is related with strain types that cells were infected and with the cytokine that cells were treated. Moreover, Fas/CD95 expression was higher in cells infected with ME49 strain, whereas the phosphorylation of ERK1/2 was higher in cells infected with RH strain. These results indicate that in BeWo cells the incidence of apoptosis in associated to strain type of the parasite as a potential evasion mechanism for the T. gondii survival.